Role of cell rearrangement and related signaling pathways in the dynamic process of tip cell selection - Yaru Guo; Shihan Zhang; Dandan Wang; Boon Chin Heng; Xuliang Deng (Cell Communication and Signaling, 2024)
Abstract Angiogenesis is a complex, highly-coordinated and multi-step process of new blood vessel formation from pre-existing blood vessels. When initiated, the sprouting process is spearheaded by the specialized endothelial cells (ECs) known as tip cells, which guide the organization of accompanying stalk cells and determine the function and morphology of the finally-formed blood vessels. Recent studies indicate that the orchestration and coordination of angiogenesis involve dynamic tip cell selection, which is the competitive selection of cells to lead the angiogenic sprouts. Therefore, this review attempt to summarize the underlying mechanisms involved in tip cell specification in a dynamic manner to enable readers to gain a systemic and overall understanding of tip cell formation, involving cooperative interaction of cell rearrangement with Notch and YAP/TAZ signaling. Various mechanical and chemical signaling cues are integrated to ensure the right number of cells at the right place during angiogenesis, thereby precisely orchestrating morphogenic functions that ensure correct patterning of blood vessels. Video Abstract